Determination of Genetic Diversity in Selected Salt Tolerance and Sensitive Wheat by Random Amplified Polymorphic cDNA - Ismail, Eman Noaman; Al-Burki, Fouad Razzaq; Majeed, Duha M.; Hasan, Suha Faraj (Iraqi Journal of Science, 2022)
The aim of this study was to investigate the genetic diversity and markers associated with salinity tolerance in three genotypes of wheat created for salt tolerance by plant breeding program, as well as two Iraqi varieties using random amplified polymorphic cDNA (RAPD-PCR) with eight primers were used. The results of RAPD marker revealed that there are genetic variations in several particular segments of various sizes between the selected genotypes and the local varieties with more genetic variation except for (OPG-09) did not appear any band with the selected genotypes and local cultivars. The results of the phylogenetic tree analysis (cluster) based on the presence or absence of DNA amplified for each primer were used to classify similar genotypes into two main groups (1H, Iraq) genotypes were clustered in first group with a genetic distance of 85% and (2H, Ibaa99) genotypes clustered in second group with a genetic distance of 84%.The results of genetic similarity based on RAPD data shows the relationship between the selected genotypes and local cultivars, the highest genetic distance was 0.428571 between the selected genotypes (1H and 2H) and the local cultivar of (I), and the lowest value was 0.066667 between the selected genotype (1H and 3H). The results confirmed the efficiency of RAPD based cDNA technique of those genotypes that are studied for determination of genetic diversity and distance among them.